Moral e ética no ambiente escolar: o que pensam os profissionais da educação e estudantes de licenciatura - Pavaneli, Camila Fernanda Dias [UNESP]; Silva, Izabella Alvarenga [UNESP]; Parra, Andressa Carolina Scandelai [UNESP]; Cruz, Luciana Aparecida Nogueira da [UNESP]; Lucatto, Lara Cucolicchio [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
In education there is a growing interest in ethics and morals, alongside contributions that help at the construction of moral values in the school environment. However, these subjects are little discussed, nor understood by most people, including professionals working in education. We aim to investigate the initial and final conceptions on moral, ethics and rule working in school, from participants of na extension course. This course was based on the human morality theories from Jean Piaget and Lawrence Kohlberg. The assumption is that the way the education professionals conceive these concepts may interfere their pedagogical practices. The data were collected by questionnaires with 23 attendees, being 10 undergraduate students e 13 education professionals that work in public and private schools. The data analysis was done before content categorization and analysis qualitative procedures. The results show that the attendees moral and ethics concepts changed along the course. Since they had presented at first morality concepts founded in common sense of what they believed to be right, and by the end of the course started to give theoretically founded answers to comprehend the moral development.

Na área educacional há um crescente interesse pelo tema ética e moral e por contribuições que auxiliem na construção de valores morais no ambiente escolar. Porém, esses assuntos ainda são pouco discutidos, tampouco compreendidos pela maioria das pessoas, inclusive profissionais que atuam na educação. Objetivamos investigar as concepções iniciais e finais sobre moral, ética e trabalho com regras na escola, de participantes de um curso de extensão. Este curso teve como base as teorias da moralidade humana de Jean Piaget e Lawrence Kohlberg. Partimos do pressuposto de que a forma como os profissionais da educação concebem estes conceitos pode interferir em suas práticas pedagógicas. Os dados foram coletados por meio de questionários com 23 participantes, sendo 10 estudantes de licenciaturas e 13 profissionais da educação que atuam em escolas públicas e particulares. A análise dos dados se deu mediante procedimentos qualitativos de categorização e análise de conteúdo. Os resultados demonstram que as concepções de moral e ética dos participantes sofreram mudanças ao término do curso. Uma vez que, apresentavam no início conceitos da moralidade fundadas no senso comum daquilo que acreditavam ser o correto, e ao término do curso passaram a dar respostas teoricamente fundamentadas na forma de compreender o desenvolvimento moral.
Keywords: Moral; Ethics; Continuing education; Moral; Ética; Formação continuada